The interferon-dependent orchestration of innate and adaptive immunity after transplantation. - Robb, R; Hill, G (2012)
The therapeutic GVL effect after allogeneic stem cell transplantation is limited by the development of GVHD. The ultimate aim of current research is to separate the 2 processes in a meaningful fashion. The IFNs are a pleiotropic group of cytokines that were originally recognized because of their ability to interfere with viral replication. However, it is now established that these cytokines play an important role in orchestrating both innate and adaptive immunity. Multiple studies have investigated the effects of both types I and II IFN on GVHD and GVL in preclinical transplant models. The results indicate variable effects that are dependent on the period of activity within the developing immune response, the presence and type of pretransplant conditioning and the differential mechanisms, and IFN sensitivity of immune pathology within individual target organs during GVHD. This Perspective discusses the current literature on the IFNs and their potential modulation within clinical transplantation, focusing particularly on enhancing the therapeutic GVL effects.